MULTILATERALISM OR BILATERALISM: THE EU TRADE POLICY IN AN AGE OF THE WTO CRISIS - Wróbel, Anna (Ekonomika, 2013)
Abstract. The aim of the study is to analyze the EU trade policy in the age of the World Trade Organization (WTO) crisis. In addition to the WTO membership and a number of international agreements within this organisation, the EU is a party to many bilateral trade agreements and negotiating further. It is the side effect of the protracted negotiations in the WTO under the Doha Development Round. The paper discusses the process of proliferation of bilateral trade agreements in the world economy and its importance for the EU. The article is divided into three parts. Part One identifies the determinants of the WTO crisis. Part Two discusses the process of proliferation of bilateral trade agreements in the world economy. Part Three analyzes the EU trade policy and the system of the EU preferential trade agreements. It also examines trade relations of the EU with the Republic of Korea, India, and the United States of America as an illustration of the new EU trade strategy.Key words: bilateralism, European Union, common commercial policy, World Trade Organisation